The use of local by-products for formulating diets in tropical African countries - Branckaert, R.; Tessema, S.; Temple, R.S. (International Feedstuffs Institute, 1977)
Discusses the utilization of crop residues, industrial by-products, cereal straws and crop discards routinely fed to livestock in tropical African countries, w. data on their chemical composition and nutritive value.